Test-takers' eye movements: Effects of integration aids and types of graphical representations. (June 2017) - Saß, Steffani; Schütte, Kerstin; Lindner, Marlit Annalena
Abstract: The study focuses on integration aids (i.e., signals) and their effect on how students process different types of graphical representations (representational pictures vs. organizational pictures vs. diagrams) in standardized multiple-choice items assessing science achievement. Based on text-picture integration theories each type of pictorial representation hold different cognitive requirements concerning integration processes of two representations. Further, depending on type of representation not every picture is needed to answer an item correctly. Students from fifth sixth grade (N = 60) work through 12 multiple choice items while their eye movements were recorded. Results showed that students achieved higher test scores when items were presented in an integrated format than in a non-integrated format, however, this was only true for diagrams. Eye movement data revealed that students looked longer on the graphical representations in items presented in the integrated format condition compared to the non-integrated format condition. Furthermore, relations between looking at the diagrams and achievement in the integrated format emerged. Highlights: Eye-tracking data revealed differential pattern depending on item format. Students fixated longer on graphical representations in an integrated format. Fixation time on diagrams is related to achievement.